Targeting T cell (oxidative) metabolism to improve immunity to viral infection in the context of obesity - Greene, Elizabeth; MacIver, Nancie J. (Frontiers in Immunology, 2022)
Disorders of systemic metabolism can influence immunity. Individuals with obesity are known to have increased inflammation, increased risk to select autoimmune diseases, impaired response to several infections, and impaired vaccine response. For example, over the last decade, it has become clear that individuals with obesity have increased risk of morbidity and mortality from influenza infection. Unsurprisingly, this finding is also observed in the current COVID-19 pandemic: individuals with obesity, particularly severe obesity, have increased risk of poor outcomes from SARS-CoV-2 infection, including increased rates of hospitalization, ICU admission, mechanical ventilation, and death. Several studies have now demonstrated a critical role for T cells in the context of obesity-associated immune dysfunction in response to viral infection, and one mechanism for this may be altered T cell metabolism. Indeed, recent studies have shown that activated T cells from obese mice have an altered metabolic profile characterized by increased glucose oxidation, both in vitro and in vivo following viral infection. For that reason, treatments that target abnormal immune cell metabolism in obesity may improve outcomes to viral infection. To that end, several recent studies have shown that use of the metabolic drug, metformin, can reverse abnormal T cell metabolism and restore T cell immunity, as well as survival, in response to viral infection. These findings will be discussed in detail here.